2018
DOI: 10.3390/ijms19020442
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the Right Cardiac Vagus Nerve Reduces Acetylcholine Content without Changing the Inflammatory Response during Endotoxemia

Abstract: Acetylcholine is the main transmitter of the parasympathetic vagus nerve. According to the cholinergic anti-inflammatory pathway (CAP) concept, acetylcholine has been shown to be important for signal transmission within the immune system and also for a variety of other functions throughout the organism. The spleen is thought to play an important role in regulating the CAP. In contrast, the existence of a “non-neuronal cardiac cholinergic system” that influences cardiac innervation during inflammation has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Partial hepatectomy (HpX) was conducted as described previously (Plaschke et al 2018b). Lipopolysaccharide (LPS; 20 mg/kg body weight, from Escherichia coli O111:B4, LOT 028M4022V, Sigma-Aldrich, Munich, Germany) was slowly applied via the catheter in the vena femoralis sinistra (Plaschke et al 2018a). Physostigmine as an inhibitor of the acetylcholine esterase was applied intravenously in a concentration of 0.04 mg/kg as detailed in a previous article (Plaschke et al 2016).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Partial hepatectomy (HpX) was conducted as described previously (Plaschke et al 2018b). Lipopolysaccharide (LPS; 20 mg/kg body weight, from Escherichia coli O111:B4, LOT 028M4022V, Sigma-Aldrich, Munich, Germany) was slowly applied via the catheter in the vena femoralis sinistra (Plaschke et al 2018a). Physostigmine as an inhibitor of the acetylcholine esterase was applied intravenously in a concentration of 0.04 mg/kg as detailed in a previous article (Plaschke et al 2016).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…1-2 A-F, available at https://doi.org/10.1523/JNEUROSCI.2324-19.2020.f1-2), indicating that neuronal Mfn2-regulated cardiac function, potentially through autonomic regulation, is likely an important mechanism for the suppression of lethality associated with septic shock in TMFN mice. In support of this notion, previous studies have identified autonomic control of myocardial dysfunction in LPS rodent models, particularly through cholinergic neurons of the sympathovagal system (Plaschke et al, 2018;Sallam et al, 2018;Ndongson-Dongmo et al, 2019). Nevertheless, additional work is still needed to clarify whether autonomic neurotransmission is altered by Mfn2 overexpression in neurons.…”
Section: Discussionmentioning
confidence: 86%
“…Acetylcholine is the major neurotransmitter of the vagus nerves, which innervate the liver [17,18]. It exerts parasympathetic actions by activating the acetylcholine (Ach) muscarinic M1-M5 receptors (M1R-M5R), a group of heterotrimeric G protein-coupled receptors (GPCRs) [19].…”
Section: Introductionmentioning
confidence: 99%